Faktor–Faktor yang Mempengaruhi Kejadian Hipertensi pada Lansia di RS Bhayangkara Tk. II Jayapura - Satriani Sikala; Hernandia Distinarista; Tutik Rahayu (PPNI UNIMMAN, 2025)
Elderly individuals are at risk of developing hypertension due to physiological changes, decreased body function due to aging, and past lifestyle factors such as salt consumption and physical activity. Furthermore, non-modifiable factors such as age, gender, and genetics contribute to the development of hypertension. The purpose of this study was to determine the factors influencing the incidence of hypertension in the elderly at Bhayangkara Hospital Tk. II, Jayapura. This was an analytical study with a cross-sectional design. Data were collected using a questionnaire. A total of 83 respondents were selected using simple accidental sampling. The data were statistically analyzed using chi-square analysis and multiple logistic regression. Based on the analysis results, it was found that factors that were not related to the incidence of hypertension in the elderly at Bhayangkara Hospital Tk. II Jayapura, namely age (p-value 1.000 > α (0.05), gender (p-value 0.356 > α (0.05) and history of hypertension (p-value 0.451 > α (0.05). Factors related to the incidence of hypertension in the elderly at Bhayangkara Hospital TK. II Jayapura are salt consumption patterns (p-value 0.020 < α (0.05), physical activity (p-value 0.001 < α (0.05) and nutritional status (p-value 0.042 < α (0.05). The most dominant variable influencing the incidence of hypertension in the elderly is physical activity (p value = 0.001 < α 0.05; OR = 4.196; CI 95% 1.258-13.996) and salt consumption patterns (p value = 0.020 < α 0.05; OR = 6.111; 95% CI 2.015-18.535). Physical activity and salt consumption patterns have a significant influence on the incidence of hypertension in the elderly.